A STUDY ON THE STUDENTS’ ABILITY IN USING PREPOSITION OF DIRECTION - Herdi Herdi; Nelisa Andriana (ELT-Lectura, 2017)
A few students might get confused which preposition could be properly used for certain conditions. In other word, they might be failed to distinguish the used of each preposition of direction appropriately because it has different application and meaning in sentences. Based on the syllabus of structure-one course, the students were expected to understand and to be able to use this kind of preposition correctly. Hence, the purpose of the research was to find out the students’ ability in using preposition of direction at the first year students of English Education Department, Faculty of Education and Teachers Training, Lancang Kuning University Pekanbaru for Academic Year 2016/2017. Therefore, the researcher conducted survey design to identify whether the students have understood this subject or not. Finally, the result of the study showed that the average score of students’ ability in using prepositions of direction was 66.47. In conclusion, the students’ ability in using preposition of direction was categorized into “fair” category.